Exploring students' perceptions of multicultural religious education: Strategies for promoting multicultural values in social and educational environments - Rahmania, Sheila Anisa (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Multicultural education has emerged globally as a response to the undeniable reality of multiculturalism, driven by the struggle for human rights, democracy, and equality. The diversity of ethnicities and cultures in Indonesia forms the background of this research. Diversity contributes to national development; however, issues in Indonesia also demonstrate how diversity can lead to violence and loss. Methods: This study aims to explore students' perceptions of multicultural religious education and their views on the strategies used to instill multicultural values. To ensure scientific rigor, methods such as observation, interviews, and documentation were employed, supported by relevant references. Findings: Public Vocational Secondary Schools/Sekolah Menengah Kejuruan Negeri 1 Purwokerto (SMKN 1 Purwokerto) provides dedicated spaces for each religion practiced within the school. Additionally, the school organizes a monthly